Object Recognition Supported by User Interaction for Service Robots
DOI: 10.1109/icpr.2002.1047436
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of face recognition performance with visible and thermal infrared imagery

Abstract: We present a comprehensive performance analysis of multiple appearance-based face recognition methodologies, on visible and thermal infrared imagery. We compare algorithms within and between modalities in terms of recognition performance, false alarm rates and requirements to achieve specified performance levels. The effect of illumination conditions on recognition performance is emphasized, as it underlines the relative advantage of radiometrically calibrated thermal imagery for face recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…Recognition is performed by a nearest neighbor classifier with respect to the combined score. As many previous studies have shown [1,2,4], fusion greatly increases performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognition is performed by a nearest neighbor classifier with respect to the combined score. As many previous studies have shown [1,2,4], fusion greatly increases performance.…”
Section: Resultsmentioning
confidence: 99%
“…The second one is a commercial algorithm made available for testing in binary form. 1 The training set for both algorithms was completely disjoint from gallery and probe images, provided by the authors of [4], in time, space and subjects. That is, the training set was collected at an earlier time, in a different location and used a disjoint set of subjects.…”
Section: Algorithms Testedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, face recognition in nearinfrared (NIR) [17,32] and thermal (THM) [26] spectra has been motivated by the need to determine human identity in nighttime environments [7]. Furthermore, changes in ambient illumination have lesser impact on face images acquired in these spectra than the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples include military applications such as target acquisition [20], autonomous vehicle navigation [66], collision avoidance [88], terrain analysis [69], etc. ; and surveillance applications like pedestrian detection/tracking [4], [52], face detection/recognition [43], [77], etc.…”
Section: Goals and Motivationmentioning
confidence: 99%